2011
DOI: 10.1590/s1413-70542011000400006
|View full text |Cite
|
Sign up to set email alerts
|

Estacionalidade e estabilidade de produção de forragem de progênies de Brachiaraia ruziziensis

Abstract: Conduziu-se este trabalho, com o objetivo de avaliar a produtividade de biomassa de forragem de progênies de Brachiaria ruziziensis e a estabilidade de produção ao longo de diferentes cortes, representativos de épocas favoráveis e desfavoráveis ao desenvolvimento das forrageiras. Foram avaliadas 118 progênies de B. ruziziensis, juntamente com as testemunhas B. decumbens cv. Basilisk, B. brizantha cv. Marandu, B. ruziziensis cv. Comum e Brachiaria sp., em delineamento de blocos casualisados, com duas repetições… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 7 publications
0
7
0
1
Order By: Relevance
“…Marandu differs from the genotypes evaluated, showing the largest weight, followed by hybrids C001 and R041 (Table 2). Regarding the number of vegetative tillers, genotypes X030, Y021, T026, R126, R110 and R087 showed the highest production in terms of biomass, which is an important character in the development of new cultivars (Souza-Sobrinho et al, 2005;Souza-Sobrinho et al, 2011). However, these genotypes did not show high seed yield (Tables 1, 3 and 4).…”
Section: Resultsmentioning
confidence: 94%
“…Marandu differs from the genotypes evaluated, showing the largest weight, followed by hybrids C001 and R041 (Table 2). Regarding the number of vegetative tillers, genotypes X030, Y021, T026, R126, R110 and R087 showed the highest production in terms of biomass, which is an important character in the development of new cultivars (Souza-Sobrinho et al, 2005;Souza-Sobrinho et al, 2011). However, these genotypes did not show high seed yield (Tables 1, 3 and 4).…”
Section: Resultsmentioning
confidence: 94%
“…Harvest trials are important for determining yield, regrowth capacity and management systems, as well as adaptability, stability and seasonality of production (Townsend, 2001). Seasonality in production of tropical forages is common, especially in regions with markedly dry seasons, which limits the production of dry matter (Lédo et al, 2008;Souza Sobrinho et al, 2011). For temperate forages, in addition to summer drought, the major limiting factor is the low temperature in winter (Porqueddu et al, 2005).…”
Section: Genotype X Harvest Interactionmentioning
confidence: 99%
“…Brachiaria ruziziensis) has great value for pasture diversification, particularly for milk production (Pessoa-Filho et al, 2015). This species has high nutritional quality when compared with other species of this genus (Lopes et al, 2010) and has shown potential for dry biomass yields that range from 12 to 15 tons/ha (Souza Sobrinho, Lédo, & Kopp, 2011). Moreover, this species shows adaptability to non-acid and well drained soils, tolerance to aluminum (Bitencourt et al, 2011;Martins et al, 2011), and resistance to spittlebug (Souza Sobrinho, Auad, & Lédo, 2010a).…”
Section: Introductionmentioning
confidence: 99%